SYNCHRONIZATION OF TWO COMPLEX IDENTICAL SYSTEMS USING NONLINEAR CONTROL - Panwar, Suman (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2017)
Synchronization of two complex identical system using nonlinear control is presented by this paper. For emphasis on the chaos, initial conditions sensitivity and Lyapunov exponent is calculated. For the synchronization of the complex master and slave system nonlinear control method is proposed effectively.